2017
DOI: 10.5812/jjcdc.17378
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Self-Care Program on Promoting Self-Care Behaviors in Patients with Psoriasis

Abstract: Background: Psoriasis is a chronic inflammatory disease with frequent recurrence. The associated complications cause disturbance in patients' quality of life. In addition to treatment procedures, use of self-care behaviors can be considered a cost-effective and applicable method in improving the patients' symptoms. Therefore, the present study aimed to investigate the effectiveness of a self-care program in promoting self-care behaviors of patients with psoriasis. Objectives: The present study aimed to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Additionally, agreed with Omar and Ramadan (37) who found that most studied patients had a poor level of self-care practices pre-intervention phase. This results in the same line with Karimipour et al (2) in a study entitled "The E ects of a These results were supported by Nagarajan and Thappa (38) who mentioned that the mean score in the experimental group was significantly decreased from 15.6 (±6.9) at baseline to 9.9 (±5.1) after intervention with a significant decrease in the mean disability score related to daily activities, studying/ working, personal relations, leisure time activities and treatment (pvalue < 0.001) after the intervention. In the same context Leino et al (42) in a study of "Influence of Psoriasis on Household Chores and Time Spent on Skin Care at Home" reported the greatest impact of psoriasis on activities of daily living, especially affecting clothing choice, bathing routine, and sporting activities.…”
Section: Continuing Talking About Risk Factorssupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, agreed with Omar and Ramadan (37) who found that most studied patients had a poor level of self-care practices pre-intervention phase. This results in the same line with Karimipour et al (2) in a study entitled "The E ects of a These results were supported by Nagarajan and Thappa (38) who mentioned that the mean score in the experimental group was significantly decreased from 15.6 (±6.9) at baseline to 9.9 (±5.1) after intervention with a significant decrease in the mean disability score related to daily activities, studying/ working, personal relations, leisure time activities and treatment (pvalue < 0.001) after the intervention. In the same context Leino et al (42) in a study of "Influence of Psoriasis on Household Chores and Time Spent on Skin Care at Home" reported the greatest impact of psoriasis on activities of daily living, especially affecting clothing choice, bathing routine, and sporting activities.…”
Section: Continuing Talking About Risk Factorssupporting
confidence: 92%
“…Psoriasis is associated with physical symptoms including red, scaly, itchy, and painful skin lesions, joint pain and many patients experience adverse psychological effects, including poor body image, stress, embarrassment, and depression (2) . Psoriasis can grow anywhere, but most appear on the scalp, elbows, knees, and lower back.…”
Section: Introductionmentioning
confidence: 99%